(untitled) (International Journal of Technology and Management Research, 2020)
This study set out to find the predictors of food security for vegetable producing households in the Ketu Districts of the Volta Region of Ghana. In the study area, 226 heads of vegetable farming households were purposively interviewed. The data was subsequently analysed with both food security scale score and logistic regression analysis to determine each household’s food security category. The study found eight variables as the major predictors of food security; they are: age, number of children, land ownership, access to change agent, access to financial services, number of vegetables produced, amount of credit received and vegetable produce markets. It is important that change agents focus on these factors among families to improve the availability of nutritious and adequate food in households. The other implication is that the improvement of elements such as amount of credit received and the location of vegetable markets can increase food security levels in the study site and extrapolation in other vegetable producing farm areas in the country. Keywords: Food security; predictors; credit; extension agent; land size .